Integrative analysis of metabolome and transcriptome reveals the mechanism of color formation in cassava (Manihot esculenta Crantz) leaves - Luo, Xiuqin; An, Feifei; Xue, Jingjing; Zhu, Wenli; Wei, Zhuowen; Ou, Wenjun; Li, Kaimian; Chen, Songbi; Cai, Jie (Frontiers in Plant Science, 2023)
Cassava (Manihot esculenta Crantz) leaves are often used as vegetables in Africa. Anthocyanins possess antioxidant, anti-inflammatory, anti-cancer and other biological activities. They are poor in green leaves, but rich in the purple leaves of cassava. The mechanism of anthocyanin’s accumulation in cassava is poorly understood. In this study, two cassava varieties, SC9 with green leaves and Ziyehuangxin with purple leaves (PL), were selected to perform an integrative analysis using metabolomics and transcriptomics. Metabolomic analysis indicated that the most significantly differential metabolites (SDMs) belong to anthocyanins and highly accumulated in PL. Transcriptomic analysis revealed that differentially expressed genes (DEGs) are enriched in secondary metabolites biosynthesis. The analysis in combi-nation of metabolomics and transcriptomics showed that metabolites changes are associated with the gene expressions in anthocyanin biosynthesis pathway. In addition, some transcription factors (TFs) may be involved in anthocyanin biosynthesis. To further investigate the correlation between anthocyanin accumulation and color formation in cassava leaves, the virus-induced gene silencing (VIGS) system was used. VIGS-MeANR silenced plant showed the altered phenotypes of cassava leaves, partially from green to purple color, resulting in significant increase of the total anthocyanin content and reduction in the expression of MeANR. These results provide a theoretical basis for breeding the cassava varieties with anthocyanin-rich leaves.